Intestinal homeostasis in the gut-lung-kidney axis: a prospective therapeutic target in immune-related chronic kidney diseases - Liu, Xinyin; Wang, Xiaoran; Zhang, Peipei; Fang, Yiwen; Liu, Yanyan; Ding, Yueyue; Zhang, Wen (Frontiers in Immunology, 2023)
In recent years, the role of intestinal homeostasis in health has received increasing interest, significantly improving our understanding of the complex pathophysiological interactions of the gut with other organs. Microbiota dysbiosis, impaired intestinal barrier, and aberrant intestinal immunity appear to contribute to the pathogenesis of immune-related chronic kidney diseases (CKD). Meanwhile, the relationship between the pathological changes in the respiratory tract (e.g., infection, fibrosis, granuloma) and immune-related CKD cannot be ignored. The present review aimed to elucidate the new underlying mechanism of immune-related CKD. The lungs may affect kidney function through intestinal mediation. Communication is believed to exist between the gut and lung microbiota across long physiological distances. Following the inhalation of various pathogenic factors (e.g., particulate matter 2.5 mum or less in diameter, pathogen) in the air through the mouth and nose, considering the anatomical connection between the nasopharynx and lungs, gut microbiome regulates oxidative stress and inflammatory states in the lungs and kidneys. Meanwhile, the intestine participates in the differentiation of T cells and promotes the migration of various immune cells to specific organs. This better explain the occurrence and progression of CKD caused by upper respiratory tract precursor infection and suggests the relationship between the lungs and kidney complications in some autoimmune diseases (e.g., anti-neutrophil cytoplasm antibodies -associated vasculitis, systemic lupus erythematosus). CKD can also affect the progression of lung diseases (e.g., acute respiratory distress syndrome and chronic obstructive pulmonary disease). We conclude that damage to the gut barrier appears to contribute to the development of immune-related CKD through gut-lung-kidney interplay, leading us to establish the gut-lung-kidney axis hypothesis. Further, we discuss possible therapeutic interventions and targets. For example, using prebiotics, probiotics, and laxatives (e.g., Rhubarb officinale) to regulate the gut ecology to alleviate oxidative stress, as well as improve the local immune system of the intestine and immune communication with the lungs and kidneys.